INVESTIGATING THE EFFECTS OF ERROR CORRECTION ON GRAMMATICAL ACCURACY IN B1 LEVEL LEARNERS - Nazarova Nigora Djahangirovna; Xusanova Sevara (Western European Studies, 2024)
The topic of error correction has been widely talked about in recent decades, especially by language learners and educators. The Covid-19 pandemic has only highlighted the importance of effective error correction techniques for students worldwide, increasing their value even more. Students have observed first-hand that prompt error correction can greatly improve their grammatical accuracy. This paper aims to delve deeper into the subject, specifically focusing on explaining the concept of error correction and demonstrating its role in enhancing grammatical precision in the process of language acquisition.
Keywords: Error correction; grammatical accuracy